Adsorption of Eu(III) and Th(IV) on three-dimensional graphene-based macrostructure studied by spectroscopic investigation. (May 2019) - Huang, Zhi-Wei; Li, Zi-Jie; Zheng, Li-Rong; Wu, Wang-Suo; Chai, Zhi-Fang; Shi, Wei-Qun
Abstract: One of the most important reasons for the controversy over the development of nuclear energy is the proper disposal of spent fuel. Separation of actinide and lanthanide ions is an important part of safe long-term storage of radioactive waste. Herein, a three-dimensional (3D) graphene-based macrostructure (GOCS) was utilized to remove actinide thorium and lanthanide europium ions from aqueous solutions. The adsorption of Eu(III) and Th(IV) on the GOCS was evaluated as a function of adsorption time, solution pH, initial ion concentrations, and ionic strength. The experimentally determined maximum adsorption capacities of this GOCS for Eu(III) (pH 6.0) and Th(IV) (pH 3.0) are as high as 150 and 220 mg/g, respectively. By using Fourier transformation infrared (FT-IR), X-ray photoelectron (XPS), and extended X-ray absorption fine structure (EXAFS) spectroscopy, we concluded that the Eu(III) and Th(IV) adsorption was predominantly attributed to the inner-sphere coordination with various oxygen- and nitrogen-containing functional groups on GOCS surfaces. Our selective adsorption results demonstrate that the actinide and lanthanide ions can be effectively separated from transition metal ions. This study provides new clues to the overall recycling of actinide and lanthanide ions in radioactive environmental pollution treatments. Graphical abstract: Image 1 Highlights: Adsorption capacities for Eu(III) and Th(IV) are as high as 150 mg/g at pH 6.0 and 220 mg/g at pH 3.0, respectively. Highly selective adsorption of actinide and lanthanide ions from mixed solution could be realized under acidic conditions. The inner-sphere surface complexation by -COO -, -OH, and -NH2 was revealed by utilizing batch experiments and spectroscopy. Abstract : The three-dimensional graphene-based GOCS macrostructure has a superior selective adsorption ability for lanthanide and actinide ions.